AKUNTABILITAS LABORATORIUM LINGKUNGAN DALAM MENUNJANG PENGELOLAAN LINGKUNGAN HIDUP - Anwar Hadi (Pusat Standardisasi Instrumen Kualitas Lingkungan Hidup Laboratorium Lingkungan (P3KLL), 2008)
Accountability, transparency and public participation in generate environmental quality data play a key role inthe good environmental governance principles, and the environmental quality data can be used for environmentalpolicy. To obtain valid environmental quality data which are defensible in terms of environmental regulations andscientific knowledge, repectives the data should have completeness, correctness and conformity to comply withgood environmental sampling practice and good laboratory practice according to ISO/IEC 17025: 2005. Basedon research conducted using check-list and/or surveys for 51 environmental laboratories accredited by NationalAccreditation Board showed that all laboratories do not implemented the principles of accountability yet. Besidethat the spread and quantity of the laboratories conducted environmental monitoring are not enough if compared toindustries amounts which shall be monitored. For that reason, technical assistance from, surveillance and evaluationshould be carried-out by independent and competence institution in environmental laboratory. Creating database for environmental laboratory competence by authority institution can help public for useful and optimizingthe environmental laboratories. Furthermore, establishing environmental laboratories for shall be facilitated byauthorized institution to give information each others and help solving the environmental laboratory problems